0401 Efficacy of Once-Nightly Sodium Oxybate (ON-SXB; FT218) By Narcolepsy Type: Post-hoc Analyses From the REST-ON Trial. (25th May 2022) - Dauvilliers, Yves; Roth, Thomas; Bogan, Richard; Thorpy, Michael; Morse, Anne Marie; Roy, Asim; Seiden, David; Dubow, Jordan; Gudeman, Jennifer
Abstract: Introduction: Once-nightly sodium oxybate (ON-SXB; FT218) was evaluated for treatment of narcolepsy in the phase 3 REST-ON trial (NCT02720744). Significant improvement was shown for the three coprimary endpoints mean sleep latency on the Maintenance of Wakefulness test (MWT), Clinical Global Impression of Improvement (CGI-I) rating, and weekly number of cataplexy attacks overall (all P<0.001 vs placebo) and in post-hoc analyses by narcolepsy type (NT1/NT2) for MWT and CGI-I (all P<0.05). Post-hoc efficacy analyses of objective and subjective measures of disrupted nighttime sleep and daytime sleepiness by narcolepsy type were conducted. Methods: Participants aged ≥16 years were randomized 1:1 to receive ON-SXB (1 week, 4.5 g; 2 weeks, 6 g; 5 weeks, 7.5 g; 5 weeks, 9 g) or placebo. Mixed-effects models for repeated measures were used to calculate P values for change from baseline vs placebo at weeks 3 (6 g), 8 (7.5 g), and 13 (9 g) for secondary REST-ON endpoints of Epworth sleepiness scale (ESS) score, sleep shifts (ie, the number of shifts from stages N1, N2, N3 and rapid eye movement [REM] sleep to Wake and from N2, N3 and REM sleep to N1), nocturnal arousals (NA), and patient-reported sleep quality and refreshing nature of sleep (100-point visual analog scale). Results: Of 190 participants, 145 had NT1 (ON-SXB, n=73; placebo, n=72) and 45 had NT2 (ON-SXB, n=24; placebo, n=21). Improvements with ON-SXB vs placebo were reported for shifts to a lighter stage of sleep (NT1: 6, 7.5, 9 g, all P<0.001; NT2: 6 and 7.5 g, P<0.05; 9 g, P<0.001), NA (NT1: 6 g, P<0.05; 7.5 and 9 g, P<0.01; NT2: 6 g, directional improvement; 7.5 and 9 g, P<0.05), and sleep quality (NT1: 6, 7.5, 9 g, all P<0.001; NT2: 6, 7.5, 9 g, all P<0.05). Significant improvements in ESS and refreshing nature of sleep for ON-SXB vs placebo were reported for NT1 (6, 7.5, 9 g, P≤0.001) with directional improvements observed for the NT2 subgroup. Conclusion: Results of these subgroup efficacy analyses are generally consistent with previously reported REST-ON endpoints and support ON-SXB treatment efficacy in adults with NT1 or NT2. Support (If Any): Avadel Pharmaceuticals